Ukłony… w Tanachu - Termińska, Kamilla (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The article is an analysis of the gesture of bowing in the Old Testament. A bow as a sign of homage and respect paid to God and to people of power and authority is also an axis of a multilayer communication act whose description often contains information about locution and the force of illocution. In contrast to the formalization which bows underwent in the liturgy of the Roman Catholic Church after Vaticanum Secundum, (v. Addendum), the gesture became banal in modern everyday life, but the word denoting it has gained a new reified meaning in the Polish language.